BAURAN PEMASARAN JASA TERHADAP KEPUASAN PASIEN RAWAT JALAN REHABILITASI MEDIK FISIOTERAPI RUMAH SAKIT UNDATA PALU - PEONI, MICHAEL (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to find out information related to outpatient services Rehabilitation of Physiotherapy in Undata Palu Hospital. The variables in this research are product (X1), price (X2), place (X3), promotion (X4), person (X5), physical evidence (X6) and process (X7). While the dependent variable is patient satisfaction (Y). This type of research is quantitative. The method of this research is descriptive causal. The sample used in this research is as much as 98 respondents with the form of sampling using purposive sampling technique. Data analysis used in this research is multiple linier regression analysis method. The results of this study indicate that simultaneously a mix of services consisting of products, places, promotions, people, evidence and a significant process to patient satisfaction outpatient medical rehabilitation hospital Undata Palu. And partially there is no relationship between product variables, price, promotion, people and facts with patient satisfaction, while the relationship variable and patient satisfaction.